Lenalidomide is safe and active in Waldenström macroglobulinemia. Issue 11 (6th October 2015) - Fouquet, Guillemette; Guidez, Stéphanie; Petillon, Marie‐Odile; Louni, Chanaz; Ohyba, Bella; Dib, Malek; Poulain, Stéphanie; Herbaux, Charles; Martin, Audrey; Thielemans, Béatrice; Brice, Pauline; Choquet, Sylvain; et al.
<x xml:space="preserve">Abstract</x> Lenalidomide is manageable and effective in multiple myeloma, particularly in elderly patients. Surprisingly, the combination of lenalidomide with rituximab produced clinically significant anemia at 25 mg/day for 21/28 days, the highest possible dose, in Waldenström's Macroglobulinemia (WM). We aimed to determine the maximum tolerated dose (MTD) of single agent lenalidomide and determine its impact on WM. RV‐WM‐0426 is a multicenter dose escalation open label phase 1/2 study of lenalidomide in relapsed/refractory WM (RRWM). Lenalidomide was given orally 21/28 days per cycle for 1 year, at escalated dose of 15 to 20 mg during phase 1 to determine the MTD; the phase 2 part was conducted at the MTD. Seventeen RRWM patients were included. The MTD was established at 15 mg/day 21/28. By ITT analysis, the overall response rate was 29%. With a median follow‐up of 36 months, median TTP was 16 months (95% CI 5.5–26), the 5‐year OS was 91%. The most frequent adverse events ≥ grade 3 at 15 mg were 14% anemia and 43% neutropenia. The MTD of lenalidomide is 15 mg/day 21/28 days in RRWM. Lenalidomide is active in the treatment of RRWM and the safety profile appears manageable. Future studies may look into combinations of lenalidomide and continuous dosing. Am. J. Hematol. 90:1055–1059, 2015. © 2015 Wiley Periodicals, Inc.